The Role of Digital Transformation as Moderator in the Relationship Between Intellectual Capital and the Performance of Medium Enterprises Through Organizational Learning in Badung Regency - Ganawati, Nengah; Suriani, Ni Nyoman; Yogiarta, I Made (PT FORMOSA CENDEKIA GLOBAL, 2024)
The suboptimal management approach with a humanistic perspective, particularly in developing intellectual capital, contributed to the low performance of Medium Enterprises amid rapid organizational changes. Intellectual capital became crucial in adapting to globalization, where MSMEs needed to navigate external threats and opportunities. This study examined digital transformation's role in moderating the relationship between intellectual capital and medium enterprises' performance through organizational learning. Using SEM with SmartPLS 3.0, a sample of 99 medium enterprises was analyzed. Results indicated: 1) High intellectual capital improved organizational learning, 2) Neither intellectual capital nor organizational learning directly improved performance, 3) Digital transformation strengthened the impact of intellectual capital and organizational learning on performance.